Determining flow resistance through vegetation canopy. (2nd May 2020) - Falkenstein‐Smith, Ryan; McGrattan, Kevin
Summary: This study documents the measurement of the wind resistance of different types of vegetation. The measurements are made in a wind tunnel with a 2.0 m test section and 0.5 m by 0.5 m cross‐section. Samples of vegetation have been cut into cubical volumes that span the cross‐section of the tunnel. The wind resistance is inferred via measurement of the pressure drop across the sample at wind speeds ranging from 2 to 8 m/s. The average drag coefficient of all sample configurations was determined to be 2.8 with an expanded uncertainty of 0.4. A random‐effects one‐way ANOVA was implemented on the drag coefficients of different vegetation samples. The analysis yielded a significant variation among the species. Further examination using a Tukey's test, showed only a single difference between vegetation two species. Despite the significant difference, the average drag coefficient of each species was still within the uncertainty bounds of the overall average drag coefficient, suggesting that the significant difference may not be large enough to have a practical implication.